THE STRUGGLE OF THE AFRICAN-AMERICAN FEMALE CHARACTER IN MARGOT LEE SHATTERLY’S NOVEL HIDDEN FIGURES - Tiara Febrianti; Agnes Setyowati H; Ni Made Widisanti S (Journal Albion : Journal of English Literature, Language, and Culture, 2019)
AbstractThe main topic of this research is the struggle of an African-American woman in facing discriminatory treatment.  It is a study on the main character in Margot Lee Shetterly's novel: Hidden Figures. The process of this research involves the overall story, intrinsic elements: character and characterization, conflict, setting and plot and also extrinsic elements: liberal feminisme, multicultural feminism and racism. This qualitative research is conducted by applying descriptive analysis method along with library research technique, leading to the identification that racism and feminism turns out to cause discrimination. The main character, Katherine, undergoes dicrimination on  education and employment for African-American people. These experiences eventually prompts the main character to fight against discrimination by proving that she is capable of becoming the first black woman who works for NASA.Keywords : discrimination, female main chracter, feminism, racism, struggle